Urtikaria pada Perawat di Bangsal COVID-19: Laporan Kasus - Rita Ingewaty Wijaya; Dewi Sumaryani Soemarko (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Chlorhexidine is widely used in health centers as an antiseptic and disinfectant. Several cases of immediate and delayed hypersensitivity to chlorhexidine have been reported. Case report: We reported a case of a 26-year-old nurse working in Hospital X that came with a complaint of itch in several areas of the body that started four days before presenting at the hospital. The itch was continuously felt, and it started to form multiple large red bumps. Redness accompanied by dry skin was present between the fingers and palms. Cetirizine and dexamethasone did not relieve the symptoms. The patient has been working for six years in the inpatient unit and six months in the COVID-19 ward. Since the pandemic, she had been using alcohol-based hand rubs more frequently. The hospital uses chlorhexidine as an alcohol-based hand rub, which may cause hypersensitivity reactions to exposed health workers. The patient was finally diagnosed with acute urticaria. Based on the seven steps of occupational diagnosis of disease, it was still inconclusive whether the urticaria is an occupational disease because there was no data regarding the causal relationship between chlorhexidine exposure and the incidence of urticaria. Conclusion: Hence, it is necessary to carry out further diagnostic test with a puncture test. The hospital is still required to implement control measures toward chlorhexidine exposure.